Interface elements of an online classroom platform for students with visual perceptual disabilities / Zazaleena Zakariah, Nawal Abdul Razak and Khadijah Ahmad Tajuddin - Zakariah, Zazaleena; Abdul Razak, Nawal; Ahmad Tajuddin, Khadijah (UiTM Press, 2023)
For a significant amount of time, due to the pandemic of Covid-19, most classes were conducted online through online classroom platforms where students and teachers did not need to physically attend classes. The wide use of online classroom platforms involved all levels of students from preschool to higher education level. These included students with disabilities as well. Most issues arise due to most online classroom platforms not focusing on different types of students, especially students with special needs. Preliminary findings show that most of the platforms designed do not meet the needs of students with disabilities. For this study, the focus is given to students with visual perceptual disabilities. Previous research proved that students with visual perceptual disabilities mostly faced issues that deal with interface elements that include the selection of color, font, size, and design. These issues make their learning process challenging. Hence this study has been carried out with two objectives which are to identify the visibility issues for students with visual perceptual disabilities with the current interface of online learning platforms and to identify the interface elements that suit their needs. Findings from this study can be used as a guideline in developing the interface of an online learning platform for visual perceptual disabilities students. This study will bring a positive change in the life of students with visual perceptual disabilities as they will be able to use the online classroom with ease.